British Malaya, 1824-67 - Mills, Lennox Algernon (MBRAS reprint, 1961)
It is something of a classic, being one of the first serious historical works to study the development of British influence through the Straits Settlements of Singapore, Malacca and Penang on the Malay Peninsula, in the middle years of the nineteenth century. The study concludes in 1867, the date when the administration of the Straits Settlements was tranferred from the Indian Office to the Colonial Offie.